Age-related clinical characteristics of children and adolescents with ADHD - De Rossi, Pietro; D’Aiello, Barbara; Pretelli, Italo; Menghini, Deny; Di Vara, Silvia; Vicari, Stefano (Frontiers in Psychiatry, 2023)
Introduction Attention deficit hyperactivity disorder (ADHD) has been associated with difficulties in regulating aversion states, high functional impairment, and a high risk of psychopathology across the lifespan. ADHD is clinically heterogeneous, with a wide spectrum of severity and associated symptoms. Clinical characteristics need to be carefully defined in different periods of life as ADHD course, symptoms, and comorbidities may fluctuate and change over time. Adolescence usually represents the transition from primary to secondary education, with a qualitative and quantitative change in environmental and functional demands, thus driving symptoms’ change. Methods In order to characterize age-related clinical features of children (<11 years) and adolescents (≥11 years) with ADHD, we conducted a naturalistic study on 750 children and adolescents assessed for ADHD at our Neuropsychiatry Unit over the course of 3 years (2018–2020). Results We found that ADHD symptoms were significantly higher in children than adolescents. More importantly, we found worse global functioning, lower adaptive skills, higher levels of anxiety and depressive symptoms, somatic complaints, emotional dysregulation, social problems, and aggression in adolescents, despite a lower severity of ADHD-specific symptoms. Conclusion These results should be confirmed in longitudinal observational studies of adequate sample size in order to reliably describe a potential course characterized by worsening of functioning, reduction in ADHD-specific symptoms and increase in general psychopathology during the transition from childhood to adolescence.